2017
DOI: 10.1097/sla.0000000000002366
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic Induction Therapy Improves Clinical Outcomes in African-American Kidney Transplant Recipients

Abstract: Objective Determine the impact of cytolytic versus IL-2 receptor antibody (IL-2RA) induction on acute rejection, graft loss and death in African-American (AA) kidney transplant (KTX) recipients. Background AAs are underrepresented in clinical trials in transplantation; thus, there is controversy regarding the optimal choice of perioperative antibody induction in KTX to improve outcomes. Methods National cohort study using US transplant registry data from January 1, 2000 to December 31, 2009 in adult solita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The strengths of this study lie in the use of a large multicenter registry and adjusting for era effect. Though this is the first pediatric heart transplantation analysis showing race‐specific benefit of ATG over BAS induction, similar results have been observed in black renal transplant recipients, and some adult heart transplant analyses have demonstrated race‐specific benefit of ATG induction …”
Section: Discussionsupporting
confidence: 71%
“…The strengths of this study lie in the use of a large multicenter registry and adjusting for era effect. Though this is the first pediatric heart transplantation analysis showing race‐specific benefit of ATG over BAS induction, similar results have been observed in black renal transplant recipients, and some adult heart transplant analyses have demonstrated race‐specific benefit of ATG induction …”
Section: Discussionsupporting
confidence: 71%
“…In contrast, higher mortality for IL2rAb versus TMG was not confirmed in subgroup analyses. With regard to outcomes in specific subgroups, a recent retrospective analysis of African American kidney transplant recipients identified in US registry data found that, compared to IL2rAb induction, depleting induction (including TMG, ALEM, or OKT3) was associated with 32% reduction in acute rejection, 9% lower graft loss, and 12% lower mortality over up to 14 years of follow‐up . Another registry‐based study focused on retransplant recipients, and found that compared to patients induced with TMG, no induction was associated with 82% greater adjusted likelihood of early acute rejection, while IL2rAb induction was associated with more than twice the likelihood of early acute rejection .…”
Section: Discussionmentioning
confidence: 99%
“…This guideline also recommended IL2rAb for first‐line induction therapy (1B), while offering a class 2B recommendation for use of cell‐depleting agents in patients considered “high risk” for acute rejection. Increased immunological risk has been associated with black race, allosensitization, retransplantation, and younger age . Recipients of organs believed to be at greater risk of delayed graft function or rejection, such as more donor–recipient human leukocyte antigen (HLA) mismatches, longer cold ischemic time, and higher kidney donor profile index, may also warrant stronger induction therapy .…”
Section: Introductionmentioning
confidence: 99%
“…In the current era of DCD, given the weaker immunosuppressive potency of non-depleting treatment compared to lymphocyte-depleting drugs, basiliximab use is limited to recipients at high risk of AR or DGF ( 14 ). In addition, while the depleting rATG effectively inhibits the incidence of AR, it also increases the risks of corresponding complications such as lymphopenia and infection ( 15 , 16 ); however, little is known about its effects on the lymphocyte populations ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%